2018
DOI: 10.1038/s41598-018-29212-0
|View full text |Cite
|
Sign up to set email alerts
|

Volatile compounds emission from teratogenic human pluripotent stem cells observed during their differentiation in vivo

Abstract: Several investigations point out that the volatile fraction of metabolites, often called volatilome, might signal the difference processes occurring in living beings, both in vitro and in vivo. These studies have been recently applied to stem cells biology, and preliminary results show that the composition of the volatilome of stem cells in vitro changes along the differentiation processes leading from pluripotency to full differentiation. The identification of pluripotent stem cells is of great importance to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Octane-4-methyl was found at altered concentrations in the breath of patients affected by colorectal cancer (41) and lung cancer (42), while the content of nonanal in breath has been related to lung cancer (30) and ovarian cancer (43). Furthermore, both these compounds are also present among those VOCs signaling the differentiation of pluripotent stem cells (44). Here, we found that nonanal and octane-4-methyl are also released by saline injected mice, thus these compounds are likely related to normal metabolic processes and amplified by the injection of DLD-1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Octane-4-methyl was found at altered concentrations in the breath of patients affected by colorectal cancer (41) and lung cancer (42), while the content of nonanal in breath has been related to lung cancer (30) and ovarian cancer (43). Furthermore, both these compounds are also present among those VOCs signaling the differentiation of pluripotent stem cells (44). Here, we found that nonanal and octane-4-methyl are also released by saline injected mice, thus these compounds are likely related to normal metabolic processes and amplified by the injection of DLD-1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Similar sensor arrays were used in recent years to measure the volatile compounds released by murine models to study gene knockdown in colon cancer, 184 the differentiation of pluripotent human stem cells, 185 and the progression of malaria infection. 186 A further example of the electronic nose was given by an array of four resistive porphyrins and corroles-functionalized ZnO nanoparticles assembled and tested as compared to various volatile compounds and real samples too.…”
Section: Sensor Arrays and Electronic Nosesmentioning
confidence: 99%
“…These sensors have been used in several metabolomics studies. For instance, they have been used in breath analysis to detect lung cancer (Gasparri et al, 2016;Di Natale et al, 2003) and tuberculosis (Zetola et al, 2017), to study in vivo and in vitro the differentiation processes of stem cells (Capuano et al, 2017;(Capuano et al, 2018) ), to study the volatile compounds of a murine model of cancer related protein knockdown (Murdocca et al, 2019), and to analyze the volatile compounds released by malaria murine models (Capuano et al, 2017) and malaria infected human erythrocytes (Capuano et al, 2019).…”
Section: Sensor Arraymentioning
confidence: 99%